Social comparison modulates the neural responses to regret and subsequent risk-taking behavior. Issue 10 (24th August 2018) - Liu, Zhiyuan; Zheng, Li; Li, Lin; Xu, Jialin; Cheng, Xuemei; Guo, Xiuyan; Mulcahy, James; Xu, Min
Abstract: The current functional magnetic resonance imaging fMRI study investigated how outcomes achieved by others affect subjective regret and subsequent behavior. During the task, participants were asked to open a series of boxes consecutively until they decided to stop. Each box contained a reward (gold), except for one that contained an adverse stimulus (devil), which caused the participants to lose all the gold they collected in that trial. Importantly, participants were instructed that every trial they encountered would also be played in parallel by another player. During the feedback stage, outcomes of both the participant and the other player were presented. Behaviorally, participants felt less regret and took less risk when objective outcomes improved or when their outcomes were better than others. Participants tended to take more risk after experiencing regret. At the neural level, the ventral striatum (VS) and the pregenual anterior cingulate cortex (pgACC) showed increased activation as objective outcomes improved. Across participants, activation of the VS was positively correlated with corresponding behavioral changes. Increased activation of the VS and significantly higher functional connectivity with the dorsal anterior cingulate cortex (dACC) were found when their outcomes were better than others. Additionally, the VS–dACC functional connectivity was correlated with risk-taking behavior.